2018
DOI: 10.22158/selt.v6n2p112
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Instagram in the Teaching of EFL Writing: Effect on Writing Ability and Students’ Perceptions

Abstract: <p class="Body"><em>This study examined the effect of the use of Instagram on EFL students’ writing ability. It involved 34 EFL students of an Indonesian university. The students were taught to write opinion essays with Instagram as the instructional medium. The treatment was given in six meetings, excluding the writing pre-test and post-test. The students were asked to make an opinion essay in the pre-test and post-test. They were also asked to respond to a questionnaire designed to verify their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
31
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 3 publications
7
31
0
3
Order By: Relevance
“…It is clear that Instagram has become an influential mode of communication for exchanging ideas and is serving as a learning resource for individual learners, including in school settings. In accordance with the present findings, recent research has highlighted that learners agree that it is enjoyable to post writing assignments on Instagram and that it is interesting to give feedback via Instagram (Handayani, Cahyono, & Widiati, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…It is clear that Instagram has become an influential mode of communication for exchanging ideas and is serving as a learning resource for individual learners, including in school settings. In accordance with the present findings, recent research has highlighted that learners agree that it is enjoyable to post writing assignments on Instagram and that it is interesting to give feedback via Instagram (Handayani, Cahyono, & Widiati, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Some previous studies have reported the emergence of the social networking sites in teaching of writing (Robertson & Adamson, 2007;Xodabande, 2018), especially by means of Instagram (Al-Ali, 2014;Aloraini, 2018;Handayani et al, 2018;Listiani, 2016). A research report from Handayani et al (2018) entitled "The Use of Instagram in the Teaching of EFL Writing: Effect on Writing Ability and Students" Perceptions" showed that the students" writing ability in writing an opinion essay improved after being taught by using mobile application Instagram as a medium of learning. The use of Instagram in teaching writing also triggers the students to communicate with their friends and offers opportunities for interaction which are meaningful and less intimidating, especially for introvert students (Aloraini, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen through the process of treatment by using Instagram. One of the supporting research conducted by Handayani et al (2018), they defined that Instagram had a positive effect on the writing ability of the students. The students found writing on Instagram is faster than paper and pen, which need a lot of time on top of their other activities.…”
Section: Discussionmentioning
confidence: 98%